The education reform at the subnational level: harmony and dissonance - Rojas, Javier (Convergencia Revista de Ciencias Sociales; Núm. 78 (2018): Convergencia Revista de Ciencias Sociales núm. 78 septiembre-diciembre 2018, 2018)
The educational reform launched in 2013 in Mexico inaugurated a teachers’ evaluation system based on the premise that it would improve the quality of education. After examining the political reform behind this framing that reconfigured the corporatist pact between the State and Sindicato Nacional de Trabajadores de la Educación, this research measures the timeliness and consistency with which local congresses harmonized their education laws according to the national normative framework. Using legislative harmonization protocols, the article proposes a method to measure normative changes and identify challenges associated with the implementation of public policies. Results suggest that opposition to the educational reform in terms of normative frameworks is geographically clustered, therefore this article offers some hypotheses to explain variations in the timeliness, compliance and consistency of the harmonization processes involved in implementing the reform at a subnational level.